2018
DOI: 10.1186/s13256-018-1888-4
|View full text |Cite
|
Sign up to set email alerts
|

Secondary extramedullary plasmacytoma of sigmoid colon in a patient with multiple myeloma: a case report

Abstract: BackgroundExtramedullary plasmacytoma is an uncommon tumor that most often involves the nasopharynx or upper respiratory tract. Extramedullary plasmacytoma is a type of plasma cell neoplasm that can present as a primary tumor or secondary to another plasma cell neoplasm, such as multiple myeloma. Secondary extramedullary plasmacytoma is usually noted in the advanced stages of the disease. Involvement of the gastrointestinal tract occurs in approximately 10% of cases.Case presentationA 71-year-old Caucasian wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…EMP can be divided into two types: Primary and secondary. EMP can also present as a secondary tumor of another plasma cell neoplasm, such as MM[ 15 ]. MM must be excluded before the diagnosis of primary EMP[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMP can be divided into two types: Primary and secondary. EMP can also present as a secondary tumor of another plasma cell neoplasm, such as MM[ 15 ]. MM must be excluded before the diagnosis of primary EMP[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary plasmacytoma occurs in around 3-20% of plasmacytomas in various studies, and involvement of the colon is rare. 1,8 It is commonly seen in upper respiratory tract (82%) with the rest in the urinary bladder, brain, thyroid, skin, etc. Involvement of GI tract is seen in less than 10% of cases, frequent in the small intestinal tract, followed by the stomach colon and esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown surgical intervention has good outcomes, and radiation therapy is used if surgery is not indicated. 1 The use of adjuvant chemotherapy is recommended for patients with higher-grade disease, tumor size >5 cm, or refractory disease. The prognosis of GI involvement is unknown; however, studies have indicated a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations